Pengaruh Pembelian Online Di Shopee Terhadap Perubahan Gaya Hidup Konsumtif Perempuan - Fina Melia Yulifan Senja (Economie: Jurnal Ilmu Ekonomi, 2023)
Online shopping is a phenomenon that has become a way of life for people. The convenience and comfort felt by consumers and the experience created by online shopping has made this phenomenon increasingly developed in society. This has led to an increase in consumptive behavior that does not discriminate between groups, so that students who don't have a job can also be ensnared, where on the other hand the developments and innovations that are unceasingly increasingly support this phenomenon, such as the increasingly widespread marketplace for online shopping, one of the only Shopee that creates convenience, enjoyment and experience for its consumers. This study aims to see how the convenience, enjoyment, and experience created by shopping online through Shopee affect the consumptive behavior of students, especially female students. The method used in this study is a quantitative approach and uses multiple linear regression analysis techniques. The results of the study show that the ease and convenience of online shopping partially affect consumptive behavior, while the online shopping experience has no effect on consumptive behavior. Meanwhile, simultaneously, convenience, comfort, and online shopping experience affect consumptive behavior with a contribution of 14.4%.